POLITICAL DIALOGUE IN THE CONDITIONS OF GLOBALIZATIONAL CHANGES - Denysiuk, Anastasiia (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2022)
The article analyzes the possibility of implementing a political dialogue between states in the context of globalization. Attention is drawn to the existence of states of different types, differing in political regimes and traditions. This situation complicates communication between them and making effective decisions for all participants in the interaction. A political dialogue is modeled between states that differ in resources and degree of influence. They consider mechanisms for building a dialogue between states in order to maintain a balance between defending the interests of citizens and realizing the values ​​of globalization. Attention is focused on the fact that it is necessary to form and consolidate at the international legislative level the functions and methods of influence of a superstate organization that would act as a guarantor of the security of each state and create conditions for maintaining and implementing the results of a political dialogue.The prospects for asserting the authority of Ukraine in international relations are considered. Actual tasks are systematized, the solution of which will help Ukraine get the role of an influential state in a globalized world. We are talking about improving the legal framework, developing effective mechanisms for harmonizing domestic law with Western European law. It is important to introduce effective organizational and legal mechanisms of state administration and minimize the commercialization of the information space.It is substantiated that it is necessary to form an international parliamentary group that would deal with issues of coordination of global socio-economic policy. It is noted that it is important to consolidate at the international legislative level the functions and methods of influence of the supranational organization, which would be the guarantor of world security and would create conditions for conducting and implementing political dialogue.